2021
DOI: 10.1088/1755-1315/724/1/012064
|View full text |Cite
|
Sign up to set email alerts
|

Carbon stocks of Petungkriyono mixed forest as climate change mitigation

Abstract: The Petungkriyono forest covers 53.88 km2 at Pekalongan Regency with 54.6% composition of mixed forest (29.43 km2). This study aimed to estimate above-ground biomass and carbon stocks from five villages; Tlogopakis, Tlogohendro, Kayupuring, Yosorejo and Kasimpar. Non-destructive samples of 30 plots were conducted by designing plots with 0.04 ha and stand inventory involving diameter at breast height, height and number of trees. The result showed that the total estimated biomass from five villages was 3,006.10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…With an area of 7,359 hectares, it is situated in the southeast of the district, around 34 kilometers from Pekalongan, the district capital. Compared to other sub-districts in the Pekalongan district, this one has the lowest temperature (18-30 °C) (Damayanti et al, 2021a;Pradana et al, 2020). This is because the area is mostly covered in forests and has a high altitude of approximately 1,294 meters above sea level (BPS Pekalongan Regency, 2023).…”
Section: The Sosiogeography Of Petungkriyonomentioning
confidence: 99%
See 2 more Smart Citations
“…With an area of 7,359 hectares, it is situated in the southeast of the district, around 34 kilometers from Pekalongan, the district capital. Compared to other sub-districts in the Pekalongan district, this one has the lowest temperature (18-30 °C) (Damayanti et al, 2021a;Pradana et al, 2020). This is because the area is mostly covered in forests and has a high altitude of approximately 1,294 meters above sea level (BPS Pekalongan Regency, 2023).…”
Section: The Sosiogeography Of Petungkriyonomentioning
confidence: 99%
“…It is situated between 700 and 1500 meters above sea level (masl). (Damayanti et al, 2021a). According to some (Damayanti et al, 2021b(Damayanti et al, , 2018, Petungkriyono is the last remaining high biodiversity tropical forest in Java.…”
Section: The Flora Of Petungkriyono Forest : Iucn Conservation Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there is potential for production forests in the form of Pinus merkusii, Sengon and Aren (Arenga pinnata) which are cultivated on community-owned lands. Based on the study of [6], it is possible that the Petungkriyono mixed forest has a significant potential for reducing the effects of climate change by sequestering carbon due to its carbon stocks capacity up to 1,769,390.46 Mg. Moreover, [7] conducted a study to calculate the total economic value of Petungkriyono forest and found that the entire economic value of water value, landslide prevention structures, and carbon sequestration is IDR.163.065.858.080, and the Extended Benefit Cost Ratio in Petungkriyono is 281.35%.…”
Section: Introductionmentioning
confidence: 99%